Effect of using cemented sand as a replacement layer beneath a strip footing. Issue 1 (1st January 2021) - El-Hanafy, Ahmed M.; AbdelAziz, Mohammed H.
ABSTRACT: Soil replacement is an effective technique used in construction practices. Hence, several studies have considered the mechanisms to remove and replace mitigation in the past. This research represents an analysis of the efficiency of cemented stabilized soil replacement for improving the behaviour of weak soil. On the other hand, the optimum design for foundation depends on the soil properties beneath these foundations. One of the best solutions for this challenge is to increase the shear parameters and reduce the compressibility for the foundation soil using cemented sand mixture technique. An experimental program was conducted to study the impact of cement stabilization on the geotechnical characteristics of sandy soils, furthermore, five cement ratios (3%, 5%, 7%, 10% and 15% by dry weight of sand) have been mixed with sandy soil and tested under compaction and shearing. The results illustrated that the maximum dry unit weight of sand increases with the increase in cement content whereas the optimum moisture content decreases marginally with the increase in the cement content. In addition, increasing cement content leads to an increase of cohesion, friction angle and Young's modulus. This paper is considered a serious attempt to estimate the optimum cement ratio required to improve the mechanical properties of soil replacement under a strip footing. Numerical modelling for this footing was done by Plaxis software. The results illustrated that adding the cement mixture improves the behaviour of footing. The effect of the replacement extension on the strip footing is also analyzed, where; the results indicated that the optimum replacement extension is equal to the thickness of replacement. This study is based on the limitation of the herein proposed numerical model and its properties.